Pain, pleasure, and the greater good: from the Panopticon to the Skinner box and beyond - Gere, Cathy (The University of Chicago Press, 2017)
Introduction: diving into the wreck -- Trial of the archangels -- Epicurus at the scaffold -- Nasty, British, and short -- The monkey in the Panopticon -- In which we wonder who is crazy -- Epicurus unchained -- Afterword: the restoration of the monarchy